Studies on ZnO based diluted magnetic semiconductors - Deka, Sasanka; Joy, P. A. (TMS 2008 Annual Meeting Supplemental Proceedings, 2008)
The observation of ferromagnetism in the transition metal (TM) doped wide band gap nonmagnetic semiconductor ZnO opened up a new area of research because of the potential applications in spintronics devices. These ZnO based diluted magnetic semiconductors (DMS) combine their transport and optical properties with magnetism. We have carried out synthesis and studies on the magnetic and optical properties on TM doped ZnO powders in nanocrystalline form. Our studies give evidence for the origin of ferromagnetism as extrinsic due to the presence of metal nanoclusters as secondary phases in the Co and Ni doped ZnO systems although the optical and electronic structure studies indicate the incorporation of divalent metal ions inside the ZnO crystal lattice.

Structural, magnetic, dielectric and magnetodielectric properties of Bi1-xCaxFe1-xMnxO3 in the morphotropic phase boundary region - Manjunath, B.; Thakuria, P.; Joy, P. A. (Materials Research Express, 2017)
Structural, magnetic, dielectric and magnetodielectric properties of Ca and Mn co-substituted bismuth ferrite, Bi1-xCaxFe1-xMnxO3 (0 <= x <= 0.4) are reported. Structural studies by Rietveld refinement of XRD patterns revealed rhombohedral R3c structure for x <= 0.11 and orthorhombic Pbnm structure for x >= 0.2. For compositions in the range 0.11 < x < 0.2, mixed phase behaviour is observed showing a morphotropic phase boundary (MPB) region. Magnetisation at room temperature increases with increasing Ca and Mn content, showing weak ferromagnetism. Coercivity and remanence initially increase and then decrease with increasing x, showing a maximum for x = 0.175 in the MPB region. Dielectric constant also shows a maximum value in the mixed phase region. Magnetodielectric (MD) studies revealed positive MD for the R3c phase and a negative MD for the Pbnm phase, showing a maximum MD (similar to 1%) for x approximate to 0.1 and crossover at x approximate to 0.175. The studies show strong interplay between the structure and properties, suggesting tuneable bismuth ferrite based compositions for magnetoelectric applications.

Structural and magnetic properties of La2Ni1-xCoxMnO6 compounds - Pramanik, Debabrata; Mukherjee, S.; Dan, Shovan; Nandy, A.; Pradhan, S. K.; Dasgupta, Papri; Poddar, Asok; Mukherjee, Manabendra; Manjunath, B.; Joy, P. A. (Materials Research Bulletin, 2018)
Single phase monoclinic La2Ni1-xMnO6 (x = 0.2, 0.4, 0.8) compounds, henceforth, referred as LNCxMO (x = 0.2, 0.4, 0.8) have been prepared by Sol-gel technique. The structural study and redox titration suggest that the samples are both La and O deficient. The generated atomic models using Rietveld refined structural parameters show octahedral distortion In the double perovskite structure. X-ray photoelectron spectroscopy (XPS) study has been used to determine the predominant valence states of Ni, Mn and Co ions. LNCxMO (x = 0.2, 0.4) are found to be Heisenberg ferromagnets whereas LNC0.8MO is a phase segregated system. In LNC0.4MO and LNO0.8MO, at temperatures above T-c, chi(-1)(T) curve shows the characteristics of Griffiths phase. The study of ac susceptibility and Isothermal remanent magnetization (IRM) discard the possibility of any glassy state at low temperatures. The antiphase boundaries (APBs), antisite disorders (ASDs) and oxygen vacancies play important roles in this system.

Stealth emulsion based on natural rubber latex, core-shell ferrofluid/carbon black in the S and X bands - Vinayasree, S.; Nair, Ajalesh Balachandran; Mani, Manoj; Archana, V. N.; Joseph, Rani; Mohanan, P.; Joy, P. A.; Anantharaman, M. R. (Nanotechnology, 2019)
A lossy dielectric with an appropriate magnetic property is one of the requirements of a stealth material. The thickness of the absorber and the corresponding bandwidth of absorption are also other deciding factors that determine the choice of the material as microwave absorbers. A stable emulsion, which is lossy as well as magnetic, is promising, since it can be coated on surfaces with required thickness in the desired band. A magnetic nanofluidic emulsion serves the purpose. A microwave absorbing emulsion based on natural rubber latex with core-shell magnetic nanoparticles, based on superparamagnetic iron oxide nanoparticles (SPIONs), was developed. The effect of additives like carbon black on the bandwidth of absorption was also studied as a function of weight percentage of carbon black. The complex dielectric permittivity and magnetic permeability were evaluated using a vector network analyser in the S and X bands. Furthermore, these results were modelled using surface impedance equations. These investigations revealed that the incorporation of carbon black enhances the bandwidth of absorption and an emulsion with the required dielectric permittivity and magnetic permeability can be tailored for stealth applications.
Keywords: carbon black; core-shell nanoparticles; ferrofluid; microwave absorbing paint; natural rubber latex

Synthesis, crystal structures, dielectric and magnetic properties of manganese sulfonyldibenzoates - Balendra; Singh, Bharti; Banday, Azeem; Tewari, Shailabh; Kumar, Vineet; Murugavel, Sevi; Joy, P. A.; Ramanan, Arunachalam (Crystengcomm, 2021)
{A systematic investigation of the system manganese(II) salt-H(2)SBA-auxiliary ligand-solvent successfully led to the isolation of six new multidimensional coordination polymers: [Mn-5(2-pic)(2)(DMA)(4)(SBA)(4)]center dot 4DMA (1), [Mn-3(pyzc)(2)(DMF)(H2O)(SBA)(2)]center dot DMF center dot H2O (2), [Mn-5(pyzc)(2)(DMA)(4)(SBA)(4)]center dot 4DMA (3), [Mn-5(mpyzc)(2)(DMA)(4)(SBA)(4)]center dot 4DMA (4), [Mn-2(phen)(2)(H2O)(SBA)(2)]center dot 2DMA (5) and [Mn-3(phen)(2)(SBA)(3)]center dot 5DMF (6), where SBA = 4,4'-sulfonyldibenzoate 2-pic = 2-picolinate